English Translation of TCM Terms of Pulse Manifestations from the Perspective of Eco-translatology –A Case Study of Seven Moribund Pulses - Liu, Shutian (Pacific International Journal, 2025)
The English translation of contemporary Chinese terms of pulse manifestation is a major academic problem in the translation of traditional Chinese medical terminology, which has a great impact on the foreign academic propaganda and research development of traditional Chinese medicine. As one of the essences of modern Chinese medicine, pulse not only has a concise form but also has a rich connotation, which makes it a great test for translators. Based on the ecological translation theory proposed by Professor Hu Gengshen, this paper analyzes the terms of pulse manifestation objectively, takes the seven moribund pulses as an example, and studies it from the perspective of translation in the three dimensions of linguistic, cultural and communicative dimensions, and refers to the current situation of research on the English translation of terms of pulse manifestation in China, to explore how to apply the ecological translation theory to the practice of English translation of terms of pulse manifestation in traditional Chinese medicine, so as to provide a new theoretical way of thinking for the development of the research of the English translation of terms of pulse manifestation in China.